Electro-Physiological Pattern And Severity Grading of Carpal Tunnel Syndrome (Journal of Dhaka Medical College, 2023)
Background: Carpal Tunnel Syndrome (CTS) is a constellation of symptoms and signs caused by entrapment of the median nerve at the wrist. Nerve Conduction Study (NCS) serve as an objective supplementary modality in the diagnosis of CTS and is used for severity assessment with high degree of sensitivity and specificity. Severity assessment is a crucial step for defining prognosis of CTS.Methodology: The study was a hospital based observational cross sectional study and was conducted in the department of Neurology, DMCH on 50 patients with clinical diagnosis of CTS with electro-physiological confirmation from July, 2017 to June, 2019. Equal number of age and sex matched healthy people were included in the study. All the cases had clinical evaluation and standardized electrophysiological studies of upper limbs using the same protocol.Result: The mean age of CTS patients was 43.06 (±10.54) years and majority of the them were female (74%). In patients with CTS, electrophysiological study of median nerve revealed the following mean value MDL=5.98± 1.63 ms, SDL=4.24± 0.59 ms, CMAP = 6.16± 3.22mv, MNCV = 54.46± 6.76 m/s, SNAP = 11.65± 13.42 ìV, In Comparison to mild to moderate CTS other than CMAP, all other parameters have significant changes. In case of moderate to severe grade of CTS, all the parameters have significant changes. Amongst the 50 CTS patients, there was bilateral involvement in 21 (42%) and unilateral involvement in 29 (58%) patient. According to electrophysiological grading, 15 (21%) were in mild group; 35 (49%) were in moderate group and 21 (30%) were in severe group. According to the clinical grading, 31 (44%) were in mild group, 25 (35%) in moderate and 15 (21%) were in severe group.Conclusion: From this study it could be concluded that CTS is more common in female. Sensory symptoms and dominant (right) hand involvement were more common. NCS provides additional and independent objective evidence in the diagnosis and severity assessment of CTS patients. Assessment of severity in CTS patients is a crucial step for defining prognosis and therapeutic measures.J Dhaka Med Coll. 2021; 30(2) : 161-166